Integrative genomic analyses identify susceptibility genes underlying COVID-19 hospitalization - Gita A. Pathak (Nature Portfolio, 2021)
Genome-wide association studies of COVID-19 have identified genetic loci affecting disease severity, but the mechanisms remain to be fully described. Here, the authors use genetically predicted transcriptome, splicing and proteome data to identify potential genes and pathways underlying COVID- 19 severity.